A modeling approach to sport volunteer satisfaction. Issue 3 (19th October 2015) - Giannoulakis, Chrysostomos; Wang, Chien-Hsin; Felver, Nathan
Abstract : Purpose: – In a currently western-dominated body of literature, the purpose of this paper is to empirically examine the relationship between motivation, experience, and satisfaction through a structural equation model. This empirical examination was performed in the context of a mega-sporting event (i.e. Asian Games), while considering sample characteristics and the cultural setting of a Middle Eastern host country (i.e. Qatar). Design/methodology/approach: – A survey was disseminated to 12 competition and non-competition venues of the 15th Asian Games in Doha, Qatar. There was a convenience sample of 392 volunteers. Findings: – Three-factor identification for volunteer motivation (external, purposive, and event related) with 48.76 percent variance explained. One-factor identification for volunteer experience with 66.08 percent of the variance explained. Two-factor identification for volunteer satisfaction (recruitment and training, communication and support) with 68.93 percent of variance explained. The sport volunteer satisfaction model fit data well (root mean square error of approximation=0.04, non-normed fit index=0.98, comparative fit index=0.99, standardized root mean squared residual=0.03). Motivation was positively and significantly related to experience. In turn, experience was positively and significantly related to satisfaction. Research limitations/implications: – Limitations included the utilization of a convenience and homogeneous sample (approximately 78 percent were Asian males), and the fact the retention construct was not included in the model. Results indicated the need to further the utilization of modeling approaches in examining psychometric properties of sport event volunteers, as well as expand the knowledge of how eastern cultures perceive the concept of volunteerism. Practical implications: – Volunteers at the Asian Games were satisfied due to the fact that their event-related motives were actually fulfilled. Participants' overall satisfaction levels were high since their experience with the event was also positive. Initially, satisfied volunteers could encourage additional volunteer involvement. An extended community-based volunteer pool could be utilized for a plethora of events in Qatar, thus supporting the country's aspiration for becoming a hub for international sport events. Originality/value: – The authors tested empirically the interrelationship between volunteer motivation, experience, and satisfaction through a structural equation model in a Middle Eastern mega-sporting event.